Phytochemicals, anti-aging, and antioxidant activities of koro komak (Lablab purpureus) on different ratios and types of solvent - Diniyah, Nurud; Dwiyanti, Inayatus Nur; Arifah, Naila Zanuba; Alshammari, Fanar Hamad; Subagio, Achmad; Novi Marchianti, Ancah Caesarina (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The aim of this study was to investigate the effect of solvent type and solvent ratio on yield, antioxidant activity (i.e., DPPH, ABTS, FRAP), total phenolics, flavonoids, anti-elastase, and tannins of Lablab purpureus (koro komak) extract. The types of solvents used were 70% of ethanol, 96% of ethanol, 22oC of water, and 75oC of water with the ratios of 1:4, 1:6, and 1:8. The experiment was conducted, duplicate and the data was obtained for analysis using ANOVA at a 95% confidence level. If the treatment shows a significant difference, DMRT is used to check for significant differences. The results indicated that the different ratios and types of solvents were giving significantly different yields, antioxidant activity, total phenolic, flavonoids, anti-elastase, and tannins. The highest yield, total phenolic, flavonoid, tannin, and antioxidant activity values were obtained from the treatment by a 1:8 ratio of 75oC of water with the value 28.39%, 11.70 mg GAE/g, 35.88 mg QE/100g, and 6.44 mg TAE/100g, 18.46 AAE/g (DPPH), 4.23 AAE/g (ABTS), and 4.17 mg Fe+/g (FRAP) respectively.